Keterkaitan pola pangan harapan (PPH) dengan kejadian stunting pada balita - Mimi Amarita (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Food security from the consumption pillar is reflected by the loyal ability of citizens to consume food that is sufficient in quantity and nutritional quality, safe, diverse and affordable. Consumption of adequate and nutritionally balanced food is a form that must be met to minimize nutritional problems including stunting.Objectives: This study aims to determine the relationship between the Expected Food Pattern (PPH) and the incidence of stunting in toddlers.Methods: The type of research used is observational research, using a cross sectional design. The research sample is 90 samples. The research location is in North Kluet District, Aceh Regency. Data analysis using SPSS Software Independent Test t-test. Research data will be presented in the form of univariate and bivariate analysis.Results: The results showed that there was no difference in the Expected Food Pattern (PPH) score between stunting toddlers and the PPH score for normal toddlers, the p value = 0.553 (p > 0.553).Conclusion: In conclusion, the PPH score in stunting toddlers with normal toddlers does not show a difference on average in North Kluet District, South Aceh.